Análisis de los efectos del impuesto al valor agregado (I.V.A.) para los consumidores finales de bajos recursos económicos de la ciudad de Quito en el último quinquenio - Rosero Díaz, Jenny Margoth (2010)
The present work is a study focused on the ultimate consumers of low income of Quito, the tax issue framed in the value added tax (VAT), to identify the effects of the adjustments that it has produced in this section population and know the conditions under which low-income people have offset these effects.